2015
DOI: 10.1016/j.jde.2014.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Eventual smoothness and asymptotics in a three-dimensional chemotaxis system with logistic source

Abstract: We prove existence of global weak solutions to the chemotaxis systemunder homogeneous Neumann boundary conditions in a smooth bounded convex domain Ω ⊂ R n , for arbitrarily small values of μ > 0.Additionally, we show that in the three-dimensional setting, after some time, these solutions become classical solutions, provided that κ is not too large. In this case, we also consider their large-time behaviour: We prove decay if κ ≤ 0 and the existence of an absorbing set if κ > 0 is sufficiently small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
122
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(127 citation statements)
references
References 24 publications
3
122
0
Order By: Relevance
“…219,119 A different aspect in the dynamics of chemotaxis-growth models has recently been addressed for parabolic-elliptic variants of (3.43)-(3.44) involving small cell diffusion. To be more precise, let us consider:…”
Section: Theorem 38 (Lankeit) Let N ≥ 3 and ω ⊂ R N Be A Bounded Domentioning
confidence: 99%
“…219,119 A different aspect in the dynamics of chemotaxis-growth models has recently been addressed for parabolic-elliptic variants of (3.43)-(3.44) involving small cell diffusion. To be more precise, let us consider:…”
Section: Theorem 38 (Lankeit) Let N ≥ 3 and ω ⊂ R N Be A Bounded Domentioning
confidence: 99%
“…To the best of our knowledge, it is yet unclear whether for n ≥ 3 and small values of μ > 0 certain initial data may enforce finite-time blow-up of solutions (cf. [22] for a high-dimensional blow-up result in a simplified chemotaxis system with superlinear logistic-type degradation), although at least certain global weak solutions are known to exist for arbitrary μ > 0 [9]. The steady-state example (u, v) ≡ ( r μ , r μ ), however, trivially shows that some global classical solutions exist regardless of the size of μ > 0.…”
Section: Introductionmentioning
confidence: 99%
“…The same result is true for τ > 0 and γ = 2 provided that n ≤ 2 or n ≥ 3 and b > b 0 with b 0 sufficiently large [12,20]. Also, in this case, for n ≥ 3, it is proved that there exists at least one global weak solution for arbitrary b > 0 [8]. Moreover, in this case when the ratio b χ is sufficiently large, it is shown that for any choice of suitably regular nonnegative initial data, there exists a unique global classical solution (u, v) such that u(., [23].…”
Section: Introductionmentioning
confidence: 56%